Chromium toxicity, speciation, and remediation strategies in soil-plant interface: A critical review - Zulfiqar, Usman; Haider, Fasih Ullah; Ahmad, Muhammad; Hussain, Saddam; Maqsood, Muhammad Faisal; Ishfaq, Muhammad; Shahzad, Babar; Waqas, Muhammad Mohsin; Ali, Basharat; Tayyab, Muhammad Noaman; Ahmad, Syed Amjad; Khan, Ilyas; et al. (Frontiers in Plant Science, 2023)
In recent decades, environmental pollution with chromium (Cr) has gained significant attention. Although chromium (Cr) can exist in a variety of different oxidation states and is a polyvalent element, only trivalent chromium [Cr(III)] and hexavalent chromium [Cr(VI)] are found frequently in the natural environment. In the current review, we summarize the biogeochemical procedures that regulate Cr(VI) mobilization, accumulation, bioavailability, toxicity in soils, and probable risks to ecosystem are also highlighted. Plants growing in Cr(VI)-contaminated soils show reduced growth and development with lower agricultural production and quality. Furthermore, Cr(VI) exposure causes oxidative stress due to the production of free radicals which modifies plant morpho-physiological and biochemical processes at tissue and cellular levels. However, plants may develop extensive cellular and physiological defensive mechanisms in response to Cr(VI) toxicity to ensure their survival. To cope with Cr(VI) toxicity, plants either avoid absorbing Cr(VI) from the soil or turn on the detoxifying mechanism, which involves producing antioxidants (both enzymatic and non-enzymatic) for scavenging of reactive oxygen species (ROS). Moreover, this review also highlights recent knowledge of remediation approaches i.e., bioremediation/ phytoremediation, or remediation by using microbes exogenous use of organic amendments (biochar, manure, and compost), and nano-remediation supplements, which significantly remediate Cr(VI)-contaminated soil/water and lessen possible health and environmental challenges. Future research needs and knowledge gaps are also covered. The review's observations should aid in the development of creative and useful methods for limiting Cr(VI) bioavailability, toxicity and sustainably managing Cr(VI)-polluted soils/water, by clear understanding of mechanistic basis of Cr(VI) toxicity, signaling pathways, and tolerance mechanisms; hence reducing its hazards to the environment.